Application of Low Doses of Ionizing Radiation in Medical Therapies. Issue 1 (3rd January 2020) - Cuttler, Jerry M.
The discovery of X-rays and radioactivity in 1895/1896 triggered a flood of studies and applications of radiation in medicine that continues to this day. They started with imaging fractures/organs and progressed to treating diseases by exposing areas to radiation from external and internal sources. By definition, low-dose treatments stimulate damage control (or adaptive protection) systems that remedy diseases. Publications are identified on low-dose ionizing radiation (LDIR) therapies for different cancers, infections, inflammations, and autoimmune and neurodegenerative diseases. The high rate of endogenous DNA damage, due to leakage of oxygen from aerobic metabolism, and the damage control systems that deal with this are discussed. Their stimulation and inhibition by radiation are described. The radium dial painter studies revealed the radium ingestion threshold for malignancy and the dose threshold for bone sarcoma. The radiation scare that misled the medical profession and the public is a barrier to LDIR therapies. Many studies on nasal radium irradiation demonstrated that children are not unduly radiation sensitive. Omissions in the medical textbooks misinform physicians about the effects of LDIR therapy, which blocks clinical trials to determine optimal doses, efficacy, and thresholds for onset of harm. Information from many recent case reports on LDIR therapies, including successes with radon therapy, is provided.